THU0475 Incomplete and Inconsistent: Investigation of Osteoporosis in A District General Hospital. (15th July 2016) - Achilleos, K.M.; Mujahid, S.; Long, P.; Hayes, F.
Abstract : Background: Osteoporosis is a disease of low bone density, micro-architectural destruction, increased bone fragility and susceptibility to low trauma fractures1, leading to increased morbidity and mortality with a 2–3 fold increased risk of further fractures 1–2 . Prompt diagnosis and optimal management of osteoporosis prevents further fractures 1–2 . The aim of screening is to identify those with greatest risk of sustaining a low trauma fracture who would benefit from intervention, as well as identifying other pathology including malignancy, presenting similarly. It is well documented that the majority of patients presenting with fragility fractures are neither appropriately assessed nor treated for osteoporosis 3–4 . Objectives: To assess compliance in screening for secondary causes of osteoporosis in all patients admitted with Neck of femur (NOF) fracture, comparing this to local CCG (Clinical Commissioning Group) guidelines. Methods: Retrospective data collection from electronic records of all patients admitted from May- July 2015 who sustained a NOF fracture. Data was collected re: screening for myeloma, hyperparathyroidism, coeliac and thyroid disease, with baseline full blood count, liver function tests, renal function, Vitamin D, bone profile and testosterone within 48hours of admission. Results: A total of 85 patients were identified as having sustained a NOF fracture during this period. 68% were female. The majority were postmenopausal (mean age: 85yrs; range: 73–99 yrs). Full blood count and renal function were performed in all, liver function tests in 64% and bone profile and vitamin D in 36% and 34% respectively. C-reactive protein was performed in 40% vs ESR in 1.2%. Only 3 and 4 patients were assessed for parathyroid and thyroid dysfunction respectively. No patient was fully screened for myeloma or coeliac disease. Of the 27 male patients all were over 70years old and none had their testosterone levels checked. Conclusions: Overall, recommended screening tests for osteoporosis were inconsistent and incomplete, which is in keeping with the current literature. Patients that were cared for in the orthopaedic and geriatric setting who have sustained a NOF fracture should have the above baseline tests. We have recommended a single tick box to encompass the above "osteoporosis bloods" on our electronic requesting system. All patients with a confirmed fracture should also be referred to our fracture liaison nurse for further evaluation and instigation of treatment. Junior doctors undergoing an orthopaedic rotation should have training in evaluating for secondary causes of osteoporosis. References: Johnell O, Kanis JA (2006) An estimate of the worldwide prevalence and disability associated with osteoporotic fractures. Osteoporosis International 17: 1726–33. Bliuc D, Nguyen ND, Milch VE, Nguyen TV, Eisman JA, Center JR (2009) Mortality risk associated with low-trauma osteoporotic fracture and subsequent fracture in men and women. JAMA 301 (5):513–521. Giangregorio L, Papaioannou A, Cranney A, Zytaruk N, Adachi JD (2006) Fragility fractures and the osteoporosis care gap: an international phenomenon. Semin Arthritis Rheum 35(5):293–305. Leslie WD, Giangregorio LM, Yogendran M, Azimaee M, Morin S, Metge C, et al. (2012) A population-based analysis of the post-fracture care gap 1996–2008: the situation is not improving. Osteoporos Int 23(5):1623–1629. Disclosure of Interest: None declared